Internalizing the Values of Hard Work Based on Bugis 3S Local Wisdom (Sipakatau, Sipakalebbi, Sipakainge) among Street Children in Makassar - Mutmainnah, Inayatul; Ibadurrahman, Ibadurrahman; Utomo, Jepri (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research aims to internalize the values of hard work based on the local wisdom of Bugis 3S (Sipakatau, Sipakalebbi, Sipakainge) among street children in Makassar, analyze its impact on their quality of life, and provide recommendations for empowerment programs rooted in local wisdom. The study employs a qualitative method with an ethnographic design to understand the cultural and social contexts of street children in Makassar, focusing on the values of hard work from Bugis 3S. Data collection involved in-depth interviews with the Social Service, street children, local communities, figures, and Bugis experts, as well as participatory observation to observe their social interactions. The next phase involved designing intervention programs based on Bugis 3S values, engaging in group discussions and interactive workshops with street children, and consulting cultural experts to ensure alignment with local wisdom. The findings indicate that collaboration among various parties in Makassar supports the internalization of hard work and moral values among street children through six strategies rooted in Bugis 3S: educational approaches, soft skills training, group work programs, public awareness campaigns, psychological support, and community involvement. These strategies aim to build character and enhance the quality of life for street children. The study concludes that the strategies based on Bugis 3S effectively instill hard work and moral values in street children in Makassar, requiring full participation from the community, government, and non-governmental organizations. This process enhances the children's ability to face life's challenges while fostering self-esteem and positive social interactions.